Aristotle, Eleaticism, and Zeno’s Grains of Millet - Boeri, Marcello D. (Peitho. Examina Antiqua, 2021)
This paper explores how Aristotle rejects some Eleatic tenets in general and some of Zeno’s views in particular that apparently threaten the Aristotelian “science of nature.” According to Zeno, it is impossible for a thing to traverse what is infinite or to come in contact with infinite things in a finite time. Aristotle takes the Zenonian view to be wrong by resorting to his distinction between potentiality and actuality and to his theory of mathematical proportions as applied to the motive power and the moved object (Ph. VII.5). He states that some minimal parts of certain magnitudes (i.e., continuous quantities) are perceived, but only in potentiality, not in actuality. This being so, Zeno’s view that a single grain of millet makes no sound on falling, but a thousand grains make a sound must be rejected. If Zeno’s paradoxes were true, there would be no motion, but if there is no motion, there is no nature, and hence, there cannot be a science of nature. What Aristotle noted in the millet seed paradox, I hold, is that it apparently casts doubt on his theory of mathematical proportions, i.e., the theory of proportions that holds between the moving power and the object moved, and the extent of the change and the time taken. This approach explains why Aristotle establishes an analogy between the millet seed paradox, on the one hand, and the argument of the stone being worn away by the drop of water (Ph. 253b15–16) and the hauled ship, on the other.